Interpretation and Performance Practice on Debussy’s Prelude No.2, Book I and Prelude No.3, Book 2 - Soratana, Ravisara; Chulapan, Panjai (Rangsit Music Journal, 2022)
This article is about interpretation and performance practice of Prelude No. 2, Book I and Prelude No. 3, Book II composed by Claude Debussy (1862-1918). The purposes of this study are 1) to study Claude Debussy’s biography and his Preludes, 2) to analyze all elements of musical structure of Prelude No. 2, Book I and Prelude No. 3, Book II, and 3) to present a guideline in practicing and performing a piano recital. The research results are 1) Prelude No. 2, Book I has complicated techniques both in producing and controlling the quality of sound; therefore, a pianist needs to produce and control 3 sound dimensions (counterpoint: ostinato, pedal, and melody) to produce light, mysterious and vague sound in order to meet the composer’s purpose. 2) Prelude No. 3, Book II has less difficult techniques; however, a pianist needs to produce proper sound quality, control and present the lively habanera rhythmic pattern in the left hand through the performance.